2019
DOI: 10.6007/ijarped/v8-i4/6497
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Higher Order Thinking and Metacognitive Skills towards Hands-On Teaching among Primary School Science Teachers

Abstract: Higher order thinking skills and metacognitive skills are essential skills in acquiring knowledge in today's challenging world. This study examined the influence of higher order thinking and metacognitive skills on hands-on teaching in science among primary school Science teachers. The first objective of this study is to determine the level of higher order thinking and metacognitive skills among science teachers. The second is to examine the relationship between higher order thinking and metacognitive skills o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
0
10
0
1
Order By: Relevance
“…Hands-on activities such as manipulating GP enables students to gain and develop constructive knowledge conception pertaining to graph sketching using the derivatives (Rohaenah et al, 2019). This finding is supported by many researchers inclusively by Sulaiman et al (2019) and Ekwueme et al (2015) which revealed that hands-on approach has significantly and positively impacted student's academic performance in mathematics, including calculus. The ability to visualize abstract concepts such as the graphic representation of a function could be developed as manipulating GP enables active cognitive engagement (Borji et al, 2018;Mendezabal & Tindowen, 2018;Orhun, 2012).…”
Section: Comparison Of Calculus Performance On Rational Function Betwmentioning
confidence: 69%
See 2 more Smart Citations
“…Hands-on activities such as manipulating GP enables students to gain and develop constructive knowledge conception pertaining to graph sketching using the derivatives (Rohaenah et al, 2019). This finding is supported by many researchers inclusively by Sulaiman et al (2019) and Ekwueme et al (2015) which revealed that hands-on approach has significantly and positively impacted student's academic performance in mathematics, including calculus. The ability to visualize abstract concepts such as the graphic representation of a function could be developed as manipulating GP enables active cognitive engagement (Borji et al, 2018;Mendezabal & Tindowen, 2018;Orhun, 2012).…”
Section: Comparison Of Calculus Performance On Rational Function Betwmentioning
confidence: 69%
“…The main principle of hands-on approach is "learning by doing" by Dewey (1938). It is supported by a famous ancient Chinese proverb of "I hear and I forget, I see and I remember, I do then I understand" (Leal-Rodriguez & Albort-Morant, 2019), which encourage students to learn through experimentation and observation (Thuneberg et al, 2018) and to build new ideas by creative and critical thinking (Sulaiman et al, 2019;Mehmood, Anwer & Tatlah, 2017;Dhanapal & Wan Zi Shan, 2013). Researchers reported that hands-on approach has significantly and positively impacted student's academic performance in mathematics (Sulaiman et al, 2019;Ekwueme et al, 2015) and science (Ekwueme et al, 2015).…”
Section: Learner-centred Interventions With Visualization and Hands-omentioning
confidence: 99%
See 1 more Smart Citation
“…HOTS merupakan keterampilan yang harus ada dalam pembelajaran sains (Sulaiman et al, 2017). Penting mengembangkan HOTS pada siswa (Hugerat & Kortam, 2014); dan melatihkan sejak dini (Zubaidah et al, 2017), HOTS dapat digunakan untuk memprediksi keberhasilan siswa (Tanujaya et al, 2017).…”
Section: Pendahuluanunclassified
“…Furthermore, primary school teachers' self-e cacy in teaching science is of great importance and can signi cantly impact students' interest and success in science-related subjects at higher education levels (Kazeni, 2021;Yildiz, 2022). The in uence of higher-order thinking and metacognitive skills on hands-on teaching in science among primary school teachers is also a critical aspect to consider (Sulaiman et al, 2019). Moreover, the hesitance of primary school teachers to teach science can be discouraging and may contribute to gaps in science education in the foundation phase (Arthur et al, 2019).…”
Section: Introductionmentioning
confidence: 99%